DIVERSITAS DAN PROFIL METABOLIT SEKUNDER JAMUR ENDOFIT YANG DIISOLASI DARI TUMBUHAN GAMBIR (Uncaria gambler) SERTA AKTIVITAS BIOLOGISNYA SEBAGAI ANTIBAKTERI - Yuliasri Jamal; Muhamad Ilyas; Atit Kanti; Andria Agusta (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Five kinds of endophytic filamentous fungi i.e. Pestalotiopsis sp. GNC, Fusarium sp. GNC-A, Fusahum sp. GNC-B, Pestalotiopsis sp. GUC and Fusarium sp. GUC were isolated from surface sterilized of steems of gambir nasi and gambir udang (Uncaria gambier Roxb.) collected from Rengat, Riau Province,Indonesia. Identification of the endophytic fungi were done through morphologically observations and chemotaxonomically approach. In an antibacterial assays, the ethyl acetate extract of the Pestalotiopsis sp.GNC cultures showed their activity against pathogenic bacteria, Eschericia coli, Staphylococcus aureus and Bacillus sublilis.Beside the above three pathogenic bacteria, the ethyl acetate extract of Fusarium sp. GNC-B culture was also active against